Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Usahatani Padi Sawah Di Kecamatan Cawas Kabupaten Klaten - Duwi Wulansari; Minar Ferichani; Rr. Aulia Qonita (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2018)
The aims of this study were to know the cost and the income of rice field farming and to analyze the influence factors in the income of rice field farming in Cawas, Klaten. The basic method that used in this study was descriptive analytics method. The study area was determined by purposive. It was done by considering the study area that had the largest rice field in Klaten. The data were collected using primary and secondary data. The result showed that: the cost commercializes of the rice field farming were used by the farmer was Rp 14.543.253/Ha, the revenue were accepted by the farmer was Rp 22.814.234/Ha, and the income that accepted by the farmer was Rp 8.270.981/Ha every season. The factors that influence to the income of rice field farming in Cawas, Klaten were labor productivity, pesticide cost, selling price, land productivity, and tractor cost. Other factors tested were age, education, experience, the number of family burden, fertilizer cost, the number of family members active in farming, and type of irrigation did not significant affected to the rice field farming income in Cawas, Klaten.